Extremely reactive carbenes: electrophiles and nucleophiles†. (26th April 2016) - Moss, Robert A.; Wang, Lei; Cang, Hui; Krogh‐Jespersen, Karsten; Abe, Manabu; Sheridan, Robert S.
Abstract : We describe the intermolecular reactivity toward alkenes of several extremely reactive carbenes as determined by experimental and computational methods. Among the examined species are the electrophiles trifluoromethylchlorocarbene and ( N ‐methyl‐3‐pyridinium)chlorocarbene and the nucleophiles adamantanylidene and dimethylcarbene. Phenomena discussed include negative activation energies for addition reactions and apparent compensation between the enthalpies and entropies of activation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We analyze trends in the measured activation parameters for the additions of representative electrophilic and nucleophilic carbenes to alkenes.